Impact of the age expansion of breast screening on screening uptake and screening outcomes among older women in BreastScreen western. (April 2021) - El-Zaemey, Sonia; Liz, Wylie; Hosseinzadeh, Negar; Lund, Helen; Mathieu, Erin; Houssami, Nehmat
Abstract: Objectives: To assess the impact of age expansion of screening (EOS) of the target age group from 50 to 69 to 50–74 in Australia, which began mid-2013, by examining screening uptake and outcomes of older women, and by identifying factors associated with continuing screening after reaching the age of 75 years. Methods: Retrospective study using data from women aged 65+ who attended BreastScreen Western Australia between 2010 and 2017 for free mammograms. Screening uptake and screening outcomes were calculated for the periods before (2010–2012) and after (2015–2017) the age EOS to women aged 70–74. Logistic regression was used to identify variables associated with continuing screening after reaching age 75 years, while controlling for possible confounding variables. Results: Age EOS increased screening uptake amongst women aged 70–74 b y 36% and amongst women ≥75 years by 3% while screening uptake in women aged 65-69 decreased by 3%. Rate of invasive screened-detected cancers significantly decreased among women aged 70–74 from 11.4/1000 screens before to 8.1/1000 screens after age EOS. Likelihood of continuing screening into age ≥75 years was higher in women who had a personal history or a family history of breast cancer, or used hormone replacement therapy within six months of screening. Women who were born outside Australia were less likely to continue screening after reaching age 75 years. Conclusions: Our study found that age EOS to women aged 70–74 was effective in increasing screening uptake in this age-group but was accompanied by a moderate increase in screening uptake amongst women ≥75 years via self-referral for whom potential benefit of screening may be limited. Highlights: In 2013 BreastScreen Australia extended the target age group from 50 to 69 to 50–74. Age expansion of screening (EOS) to women aged 70–74 increased screening uptake by 36%. Age EOS increased screening uptake for women aged ≥75 years by 3%. High risk women were more likely to continue screening after reaching age 75 years.